Impact of a physical activity program on the health-related quality of life in pediatric cancer patients: a study protocol - Gustavo Galárraga; Gustavo Galárraga; Rebecca Wurtz; Marcos Di Stefano; Marcos Di Stefano; Libet Bosch; Erika Villanueva; Karen Unda; Yunqi Yu; Carmen Apolo; Camila Coloma; José Francisco López-Gil; et al. (Frontiers in Sports and Active Living, 2025)
Physical activity is essential for the health and well-being of children and adolescents. However, those living with cancer often experience reduced physical activity levels, which negatively impact their functional capacity and health-related quality of life (HRQoL). In Ecuador, data from the National Institute of Statistics and Census (2021) reveal that 20% of children engage in less than one hour of physical activity per week, highlighting the need for targeted interventions. While previous studies demonstrate that supervised exercise programs can improve physical and psychosocial health outcomes in pediatric oncology patients, no evidence exists from Ecuador to assess the effects of such programs. This study will examine the impact of a structured physical activity program on the HRQoL of pediatric cancer patients in Quito, Ecuador. Using a case-control design, 90 participants will be randomized into two groups: an intervention group receiving a 10-week, supervised physical activity program and a control group with no exercise intervention and standard care, with additional follow-up if deemed necessary by the social worker. HRQoL surveys using a standardized instrument will be administered to all participants (those in the intervention group and those in the control group) at baseline, post intervention, and follow-up to assess changes over time. This research will address a critical public health gap by exploring how physical activity can mitigate the adverse effects of cancer treatment, improve physical and emotional health, and enhance the HRQoL in pediatric oncology patients. Findings will contribute valuable insights for integrating physical activity into pediatric oncology care in low- and middle-income countries.